B cells produce less IL-10, IL-6 and TNF-α in myasthenia gravis. (June 2015) - Yilmaz, Vuslat; Oflazer, Piraye; Aysal, Fikret; Parman, Yeşim G.; Direskeneli, Haner; Deymeer, Feza; Saruhan-Direskeneli, Güher
Abstract B cells from myasthenia gravis (MG) patients with autoantibodies (Aab) against acetylcholine receptor (AChR), muscle-specific kinase (MuSK) or with no detectable Aab were investigated as cytokine producing cells in this study. B cells were evaluated for memory phenotypes and expressions of IL-10, IL-6 and IL-12A. Induced productions of IL-10, IL-6, IL-12p40, TNF-α and LT from isolated B cells in vitro were measured by immunoassays. MG patients receiving immunosuppressive treatment had higher proportions of memory B cells compared with healthy controls and untreated patients. With CD40 stimulation MG patients produced significantly lower levels of IL-10, IL-6. With CD40 and B cell receptor stimulation of B cells, TNF-α production also decreased in addition to these cytokines. The lower levels of these cytokine productions were not related to treatment. Our results confirm a disturbance of B cell subpopulations in MG subgroups on immunosuppressive treatment. B cell derived IL-10, IL-6 and TNF-α are down-regulated in MG, irrespective of different antibody productions. Ineffective cytokine production by B cells may be a susceptibility factor in dysregulation of autoimmune Aab production.